Abnormal plasticity of sensorimotor circuits extends beyond the affected body part in focal dystonia. Issue 9 (18th July 2007) - Quartarone, A; Morgante, F; Sant'Angelo, A; Rizzo, V; Bagnato, S; Terranova, C; Siebner, H R; Berardelli, A; Girlanda, P
Abstract : Objective: To test whether abnormal sensorimotor plasticity in focal hand dystonia is a primary abnormality or is merely a consequence of the dystonic posture. Methods: This study used the paired associative stimulation (PAS) paradigm, an experimental intervention, capable of producing long term potentiation (LTP) like changes in the sensorimotor system in humans. PAS involves transcranial magnetic stimulation combined with median nerve stimulation. 10 patients with cranial and cervical dystonia, who showed no dystonic symptoms in the hand, and nine patients with hemifacial spasm (HFS), a non-dystonic condition, were compared with 10 healthy age matched controls. Motor evoked potential amplitudes and cortical silent period (CSP) duration were measured at baseline before PAS and for up to 60 min (T0, T30 and T60) after PAS in the abductor pollicis brevis and the first dorsal interosseus muscles. Results: Patients with dystonia showed a stronger increase in corticospinal excitability than healthy controls and patients with HFS. In addition, patients with dystonia showed a loss of topographical specificity of PAS induced effects, with a facilitation in both the median and ulnar innervated muscles. While PAS conditioning led to a prolonged CSP in healthy controls and patients with HFS, it had no effect on the duration of the CSP in patients with cranial and cervical dystonia. Conclusion: The data suggests that excessive motor cortex plasticity is not restricted to the circuits clinically affected by dystonia but generalises across the entire sensorimotor system, possibly representing an endophenotypic trait of the disease.